2014
DOI: 10.1016/j.jtbi.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

N-player mosquito net game: Individual and social rationality in the misuse of insecticide-treated nets

Abstract: Many governmental and non-governmental organizations have distributed insecticide-treated nets (ITNs) to malaria endemic areas, which contributed to the reduction of malaria deaths. However, some people in malaria endemic areas used ITNs for alternative purposes such as fishery and agriculture. It is unclear why people threatened by malaria misuse ITNs. Here we develop a N -player mosquito net game, and theoretically show that the misuse of ITNs might be underpinned by individual and social rationality. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Additionally, among nets within the home, less than 1% of functioning bed nets were reported as having been alternatively used in both sites. Previous reports also found rare misuse [5] and suggest it occurs for economically beneficial reasons [6,22], particularly where misused for fishing [13,14,23]. There were no observations or self-reported instances of misused nets for fishing, though interestingly nearly 50% of households in the lowlands reported seeing others using nets for fishing.…”
Section: Bed Net Misusementioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, among nets within the home, less than 1% of functioning bed nets were reported as having been alternatively used in both sites. Previous reports also found rare misuse [5] and suggest it occurs for economically beneficial reasons [6,22], particularly where misused for fishing [13,14,23]. There were no observations or self-reported instances of misused nets for fishing, though interestingly nearly 50% of households in the lowlands reported seeing others using nets for fishing.…”
Section: Bed Net Misusementioning
confidence: 72%
“…Additionally, among nets within the home, less than 1% of functioning bed nets were reported as having been alternatively used in both sites. Previous reports also found rare misuse [ 5 ] and suggest it occurs for economically beneficial reasons [ 6 , 22 ], particularly where misused for fishing [ 13 , 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We developed an evolutionary game model of the signaling strategies of a solitary prey population, such as the population of the Chinese grasshopper, based on the framework of the bednet use model for malaria protection (Honjo et al 2013;Honjo and Satake 2014). We found that the underlying mathematical structures of the bednet use model and evolutionary game model of signaling are the same and extended the former to the latter.…”
Section: Defining the Cost And Benefits Of Signalingmentioning
confidence: 97%
“…Goals of universal coverage (UC) and the methods employed to achieve UC do little to limit the presence of excess nets in distribution areas (Bhatt et al, 2015b) or to address the choices people make as to whether to use a net on their bed or for fishing (Honjo & Satake, 2014); something we need to understand much better. Aiming for universal coverage may be seen as a pragmatic approach to achieving levels of coverage that drive a 'mass effect' on mosquitoes, whereby mortality rates from insecticide contact may have a populationlevel effect and improve the effective protective range of nets (Howard et al, 2000).…”
Section: Current Policies Are Conflicting or Failingmentioning
confidence: 99%